FILSAFAT KURIKULUM MERDEKA DAN KEMANDIRIAN PENDIDIKAN - Rif'iy Qomarrullah; Lestari Wulandari S; Suratni Suratni (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
The aim of this research is to investigate the relationship between the philosophy of the Merdeka Curriculum and the empowerment of autonomy in the context of higher education. The research method involves in-depth philosophical analysis of the theoretical foundations of educational philosophy underlying the Merdeka Curriculum, with a specific focus on values such as freedom, creativity, and active student participation. This approach is used to identify how these philosophical values are reflected in the structure and design of the curriculum, as well as their impact on student empowerment. Data analysis is conducted by evaluating the philosophical concepts contained in official documents and implementation guidelines of the Merdeka Curriculum. Results and discussions indicate that the philosophy of the Merdeka Curriculum substantially supports the realization of educational autonomy by providing greater space for students to take an active role in the learning process. The conclusion of this research provides a deep understanding of how educational philosophy can be integrated into the curriculum structure to advance educational autonomy in higher education. This research contributes significantly to conceptual and practical thinking related to the empowerment of autonomy in the context of the Merdeka Curriculum.